1992
DOI: 10.1161/01.cir.85.3.928
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinopeptide A levels in patients with acute myocardial infarction treated with alteplase. Correlation with concomitant heparin, coronary artery patency, and recurrent ischemia. The European Cooperative Study Group.

Abstract: Background. Fibrin generation during and after therapy with alteplase may depend on the level of concomitant anticoagulation. The hypothesis that fibrinopeptide A (FPA) levels, as markers of ongoing in vivo fibrin formation, correlate with the angiographic and clinical outcome of thrombolysis is tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 38 publications
2
17
1
1
Order By: Relevance
“…Comparing the results obtained with the different therapies we found that more thrombin is generated in the patients treated with thrombolytics+heparin than in those receiving heparin only. This finding is in keeping with previous studies that showed an increase in thrombin generation and activity during thrombolysis with either SK or rt-PA [11,13,16,18,27]. The increase in F1+2 plasma levels observed in the SK+heparin and rt-PA+ heparin groups despite concomitant administration of intravenous heparin may relate to the reexposure of the ruptured plaque to blood flow, which might lead to the generation of more factor Xa and thrombin.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing the results obtained with the different therapies we found that more thrombin is generated in the patients treated with thrombolytics+heparin than in those receiving heparin only. This finding is in keeping with previous studies that showed an increase in thrombin generation and activity during thrombolysis with either SK or rt-PA [11,13,16,18,27]. The increase in F1+2 plasma levels observed in the SK+heparin and rt-PA+ heparin groups despite concomitant administration of intravenous heparin may relate to the reexposure of the ruptured plaque to blood flow, which might lead to the generation of more factor Xa and thrombin.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with prior studies that show an increase in some of these hemostatic markers several days after the onset of an acute coronary syndrome [1,11,16,17]. These hematological markers of the hypercoagulable state were found to relate to the subsequent risk of thrombotic events [2,11,18].…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with observations of procoagulant tendencies (eg, increase in fibrinopeptide A) induced by thrombolysis for myocardial infarction. [13][14][15] Interestingly, control subjects with vascular risk factors exhibited a significant activation of hemostasis compared with control subjects without such risk factors. Compared with risk factor-matched subjects, patients with acute ischemic stroke exhibited a significant increase in hemostatic indicators.…”
Section: Discussionmentioning
confidence: 97%